A longitudinal study of gastrointestinal parasites in English dairy farms: practices and factors associated with first lactation heifer exposure to Ostertagia ostertagi on pasture - Bellet, Camille; Green, Martin J.; Bradley, Andrew J.; Kaler, Jasmeet (American Dairy Science Association, 2018)
The gastrointestinal nematode Ostertagia ostertagi is an important cause of lost production, health, and welfare in cattle. Detailed records were obtained over a 5-yr period (2010–2015) by questionnaires and qualitative interviews to investigate the practices adopted by dairy farmers to control cattle helminth infections and the factors associated with heifer exposure to O. ostertagi on pasture. In total, 1,454 heifers' individual milk samples were collected over a 1-yr period (2014–2015) in 43 dairy farms in England and tested for O. ostertagi antibody by ELISA. Multilevel linear regression models were used to investigate the association between individual milk optical density ratio (ODR) against O. ostertagi and heifer management from birth to time of sampling. Farm and heifer median ODR against O. ostertagi were 0.98 (interquartile range = 0.76–1.02) and 0.64 (interquartile range = 0.42–0.84), respectively. The majority of heifers (88%) received an anthelmintic treatment before sampling in this study. After controlling for the effect of anthelmintic treatments, heifer individual milk ODR against O. ostertagi significantly increased with high stocking rate at first grazing and co-grazing with adult cows before calving. Conversely, heifer individual milk ODR against O. ostertagi significantly decreased when heifers had co-grazed with sheep and pasture grass had frequently been mowed. Overall, these results provide evidence to support targeting grazing management toward limiting the use of anthelmintics in dairy young stock to enable sustainable control of cattle helminth infections in England. However, to be accepted and adopted by farmers, these best practices would need to take into account farmers' perspectives and contextual challenges.